Two‐year clinical outcomes after successful transcatheter aortic valve implantation with balloon‐expandable versus self‐expanding valves: A subanalysis of the GALILEO trial. Issue 4 (30th August 2022) - Okuno, Taishi; Dangas, George D.; Hengstenberg, Christian; Sartori, Samantha; Herrmann, Howard C.; de Winter, Robert; Gilard, Martine; Tchétché, Didier; Möllmann, Helge; Makkar, Raj R.; Baldus, Stephan; De Backer, Ole; et al.
Abstract: Background: Midterm data comparing clinical outcomes after successful implantation of self‐expanding and balloon‐expandable transcatheter heart valves (THV) are limited. We aimed to compare 2‐year outcomes after successful transcatheter aortic valve implantation (TAVI) with the Edwards balloon‐expandable or the Medtronic self‐expanding THV. Methods: Two‐year outcomes were analyzed according to the implanted THV in the GALILEO trial. Major adverse cardiac and cerebrovascular events (MACCE) was a composite of all‐cause death or thromboembolic events including stroke, myocardial infarction, symptomatic valve thrombosis, systemic embolism, deep‐vein thrombosis, or pulmonary embolism. Results: Among 1644 patients recruited in 136 centers across 16 countries between 2015 and 2018, 499 received a self‐expanding and 757 patients received a balloon‐expandable THV. Patients treated with a self‐expanding THV were more likely to be female, and had higher surgical risk, lower hemoglobin levels, and more frequent valve‐in‐valve procedures than those with a balloon‐expandable THV. After multivariable adjustment, there were no significant differences in major clinical outcomes between self‐expanding versus balloon‐expandable THV: MACCE (17.0% vs. 13.4%, adjusted‐hazard ratios [HR] 1.18, 95% confidence intervals [CI]: 0.82−1.69); all‐cause death (11.4% vs. 9.3%, adjusted‐HR 1.26; 95% CI: 0.78−2.05); cardiovascular death (8.5% vs. 4.0%, adjusted‐HR 1.53; 95% CI: 0.82−2.86), any stroke (5.1% vs. 3.7%, adjusted‐HR 0.86; 95% CI: 0.43−1.73); major or life‐threatening bleeding (5.9% vs. 6.8%, adjusted‐HR 0.93; 95% CI: 0.53−1.63). Clinical Trial Registration: https://www.clinicaltrials.gov . NCT02556203. Conclusions: Two‐year follow‐up data from the GALILEO trial indicate that successful TAVI either with self‐expanding or balloon‐expandable THVs according to physician discretion did not show difference in rates of MACCE.